Hybrid Biofoam as an Alternative Insulator - S. A. Ernie;; M.K. Nurhidayah;; A.Z. Syazana (Universiti Sains Islam Malaysia, 2024)
Hybrid biofoam from polyurethane (HBPU) that exploit the tribute of natural fibers and nanoclay in green PU foam had lead to the new imminent in engaging the nanoclay and natural fibers. The hybridization of these natural fibers and oMMT permit to retain the strength without compromise the stiffness of HBPU. The hybridization also improves the barrier and thermal properties of these HBPU. Microscopic studies shows that the hybridization of these natural fibers and nanoclay provide initial evidence of the possibilities on the insertion of nanoclay into the natural fibers thus open the opportunities to exploit this behavior to another hybrid system.